Genetic polymorphism of CYP2A6 as one of the potential determinants of tobacco-related cancer risk - Kamataki, Tetsuya; Fujieda, Masaki; Kiyotani, Kazuma; Iwano, Shunsuke; Kunitoh, Hideo (Biochemical and biophysical research communications, 2005)
Analyzing the CYP2A6 gene of subjects who showed a poor metabolic phenotype toward SM-12502, we discovered a novel mutant allele ( CYP2A6* 4C) lacking the whole CYP2A6 gene. Using genetically engineered Salmonella typhimurium expressing a human CYP, we found that CYP2A6 was involved in the metabolic activation of a variety of nitrosamines such as 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) contained in tobacco smoke. Taking these results into consideration, we hypothesized that the subjects carrying the CYP2A6* 4C allele had lower risk of tobacco-related lung cancer. In accordance with our hypothesis, our epidemiological studies indicated that smokers homozygous for the CYP2A6* 4C allele showed much lower odds ratios toward cancer risk. Other mutant alleles reducing the CYP2A6 activity, besides CYP2A6* 4C, also reduced the risk of lung cancer in smokers, particularly of squamous-cell carcinoma and small-cell carcinoma, both smoking-related cancers. 8-Methoxypsoralen, an inhibitor of CYP2A6, efficiently prevented the occurrence of adenoma caused by NNK in A/J mice.